KODE FALSAFAH HIDUP ORANG MAKASSAR DALAM NOVEL SOGI: ANALISIS SEMIOTIKA ROLAND BARTHES - Andriani, Cici; Qadriani, Nurlailatul (Seshiski: Southeast Journal of Language and Literary Studies, 2024)
This study aims to find semiotic codes and analyze the meaning of codes in Faika Burhan's Sogi novel using Roland Barthes' semiology approach to find the deepest meaning in human life, especially Makassar people. The method used is a qualitative method by describing the structure of events related to Roland Barthes' code system. The results of the study show that Faika Burhan's Sogi novel uses five semiotic codes, namely (1) hermeneutic code (puzzle code) found as many as 7 data. (2) proaretic code or action code as many as 6 data. (3) connotative code found as many as 4 data. (4) symbolic code found as many as 6 data. (5) cultural code or cultural code found as many as 10 data. The five codes as a whole describe many problems, the main one being related to siri' or self-esteem which is the philosophy of life of Makassar people.